Peritoneal adhesion prevention by a biodegradable hyaluronic acid-based hydrogel formed in situ through a cascade enzyme reaction initiated by contact with body fluid on tissue surfaces. (15th September 2015) - Sakai, Shinji; Ueda, Kohei; Taya, Masahito
Graphical abstract: Abstract: Postsurgical peritoneal adhesion is a serious surgical complication. In situ hydrogel formation on the surface of tissues, which will develop adhesions, is a recent feasible approach to prevent peritoneal adhesion. Here, we report on-tissue surface formation of a hyaluronic acid-based hydrogel by administration of a pre-hydrogel aqueous solution. The hydrogelation was initiated by contact with body fluid containing glucose on tissue surfaces. During the hydrogelation, a hyaluronic acid derivative possessing phenolic hydroxyl moieties (HA-Ph) was cross-linked by a cascade reaction of glucose oxidase (GOx) and horseradish peroxidase (HRP). About 5 s of hydrogelation was accomplished using a solution containing 1.5% (w/v) HA-Ph, 5 U/mL HRP, and 2.5 U/mL GOx in 1 mg/mL glucose that is equivalent to the normal blood glucose concentration. The hydrogel was degradable by hyaluronidase and much softer than rat peritoneal sidewalls. We confirmed the efficiency of the hydrogel to prevent post-operative peritoneal adhesions by applying the solution containing HA-Ph, GOx, and HRP to animals with bowel abrasion-abdominal sidewall defects. A significant reduction in the development of peritoneal adhesions was found compared with animals applied with phosphate-buffered saline or saline containing HA-Ph alone. Statement of Significance: Postsurgical peritoneal adhesion is a serious surgical complication. In this paper, we report a novel system for preventing it through an on-tissue surface formation of a biodegradable and biocompatible hyaluronic acid-based hydrogel by administration of a pre-hydrogel aqueous solution. The in situ hydrogelation is mediated by a cascade enzyme reaction of glucose oxidase (GOx) and horseradish peroxidase (HRP) initiated by contacting with body fluid containing glucose. The efficiency of the system was confirmed by applying the system to animals with bowel abrasion-abdominal sidewall defects.